Effects of hot-water-pipeline renovation in a district heating system - Ljubenko, Andrej (Strojniški vestnik, 2011)
In this paper the attention is on the heat losses of a main, aboveground supply, hot-water pipeline, whose length is 5430 m. It is situated between the Šoštanj Thermal Power Plant (TEŠ) and the Central Energy Station (CES) Velenje as part of the district heating system in the Šaleška Valley. It was renovated because major heat losses were identified. A numerical analysis and a comparison between the temperature fields of the pipe's insulation before and after the renovation was performed to discover the main causes for the high heat losses before renovation. An integral measuring method for determining the heat losses was adapted and used to determine the pipeline's heat losses after the renovation. Taking into consideration the real operating parameters, the annual energy savings and the consequent operational cost reduction, due to the lower heat losses, resulting from the pipeline renovations, are presented. The calculation is made with measured heat-loss coefficients and is therefore based on the real state of the pipeline. The aim is to show the necessity to investigate the heat losses of a hot-water pipeline whose design or state of insulation is questionable.
Keywords: daljinsko ogrevanje; district heating; heat losses; pipeline renovation; sanacija vročevoda; thermal bridges; toplotne izgube; toplotni mostovi